Network social capital and labour market outcomes: Evidence for Ireland - Brady, Gerard (Economic & Social Studies, 2014)
Using data from the International Social Survey Programme 2008 this paper tests empirically the effects of network social capital on Irish employment outcomes, while attempting to account for possible endogeneity. We allow the effects of social networks to vary for different groups and across different localities. We find that an individual’s “weak ties” or acquaintances matter for employment outcomes, whereas their “strong ties”, for example, their friends and family, are less important. The effects, however, vary across age and location. We also find no evidence that the relationship between social participation and employment is endogenous. These findings are discussed with relevance for future research and policy.